Parental history and body mass index as predictors of osteoporosis among urban elderly women in Depok, Indonesia - Kusumawardani, Kunthi Ayu; Supartono, Basuki; Hadiwiardjo, Yanti Harjono; Citrawati, Mila (Universitas Gadjah Mada, 2025)
Purpose: This study aims to identify the risk factors associated with osteoporosis among urban elderly women in Depok, Indonesia. Methods: This research employed a cross-sectional design and involved 110 elderly women living in Cimanggis District, Depok. Participants were selected through consecutive sampling. Data were collected through interviews using the risk factor checklist from the International Osteoporosis Foundation, and bone density measurements were obtained using heel bone ultrasound. The relationship between variables was analyzed using the Chi-square test and logistic regression. Results: The results showed that most elderly suffer from osteoporosis (77.3%). BMI and parental history of hip fracture showed a significant relationship with bone density. History of fractures after 50 years of age, height loss greater than 4 cm, comorbidities, long-term medication use (over three months), smoking, and alcohol consumption showed no significant relationship with bone density. The most influential risk factor was a parental history of hip fracture. Conclusion: The majority of elderly women have osteoporosis (77.3%). Low body mass index and a family history of hip fractures are significantly associated with lower bone density. These results highlight the need for preventive strategies and lifestyle interventions to reduce osteoporosis risk among the elderly.